GEOLOGICAL EVOLUTION - STRATIGRAPHY OF FLORINA, PTOLEMAIDA, KOZANI AND SARADAPORO GRABEN - Metaxas, A.; Karageorgiou, D. E.; Varvarousis, G.; Kotis, Th.; Ploumidis, M.; Papanikolaou, G. (Bulletin of the Geological Society of Greece, 2007)
The purpose of this research is to comprehend the geological and stratigraphical evolution of Fiorina, Ptolemaida, Kozani and Sarandaporo graben. This graben extends North of the Greek borders and is more than 150 Km long. The activity of big and profound faults ofNW-SE direction, in NW Macedonia, after the end of the Alpine orogenesis cycle and during the Early Miocene was related to the formations ’ deposition. A large number of samples were collected from drill cores for the examination of palynology, paleoflora, fossils, and diatoms in order to determine the formations ’ sequence and age. The basement and the borders of the depression, belong to the Pelagonian geotectonic zone. The deposition of the Early Neogene ’s series is following. During the Late Pliocene the previous series, is developing into a lacustrine-marshland system, resulting to the deposition of Late Neogene’s series formations. In the Quartenary the following formations are deposited: Proastion formation, Perdika formation, terrestrial, fluvial-terrestrial formation, recent formation. Four (4) phases of lignitogenesis have been specified, mainly in the Ptolemaida - Amynteo basin. In this graben they have been deposited the most important lignite deposits of Greece.